Drum vermicomposting household scale as an additional source of income for farmers during the Covid-19 pandemic in Sidomulyo Village, Stabat District Langkat Regency, North Sumatra - Khairunnisa; Sebayang, Nur Ulina Warnisyah; Wahyuni, Hafnes; Sipayung, Antonio Marro; Situmorang, Sawitania C. Dwi U (Talenta Publisher, 2020)
A large amount of livestock waste, rotten fruit and vegetable waste and there is a tofu factory that produces tofu dregs around farmer's house at Sidomulyo Village, Stabat District which can be used as an innovation for farmers during the Covid-19 pandemic. The limited activities of farmers in Sidomulyo Village make it difficult for farmers to work in the field because they are worried about the spread of Covid-19 and they try to follow the government's advice to continue to do social distancing and also physical distancing. This has an impact on the income and activities for farmers who daily have to be outside the home to carry out farming activities. To get additional sources of income and positive new activities, especially during the Covid-19 pandemic, this service was carried out by utilizing livestock waste and tofu waste in the environment around Sidomulyo Village by utilizing earthworms in drums to be processed into vermicompost which can be used self (household scale) as well as being developed and marketed for the cultivation of plants such as ornamental plants or horticulture plants.